2000
DOI: 10.1097/00001813-200009000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of 2-amino-4,4α-dihydro-4α, 7-dimethyl-3H-phenoxazine-3-one against Meth A tumor transplanted into BALB/c mice

Abstract: We examined the in vivo effect of 2-amino-4,4alpha-dihydro-4alpha,7-dimethyl-3H-phenoxazine-3- one (Phx) on Meth A carcinoma cells transplanted into BALB/c mice, in terms of both antitumor activity and side effects. Phx, which was synthesized by the reaction of 2-amino-5-methylphenol with bovine hemolysates, was administered i.p. at doses of 1 and 5 mg/kg to BALB/c mice transplanted with Meth A tumor cells. Phx exerted a strong antitumor activity to Meth A tumor growing in the mice as 5-fluorouracil (5-FU) did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…Since drugs absorbed in the human body may be primarily exposed to erythrocytes circulating in the blood, before reaching the liver, where many drugs are detoxified by cytochrome P-450, our results suggest that hemoglobin in erythrocytes may play an important role in detoxifying some drugs, such as pyrogallol. We previously showed that o-aminophenol and its derivatives were metabolized to phenoxazines in human erythrocytes or by hemoglobin, and that these phenoxazines show less adverse effects in vivo using mice (Mori et al 2000), which agrees with the results of Eckert and Eyer (1983) that o-aminophenol does not exhibit nephrotoxicity due to rapid formation of the phenoxazines in dogs. Metabolism of drugs by hemoglobin have been reported by some authors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Since drugs absorbed in the human body may be primarily exposed to erythrocytes circulating in the blood, before reaching the liver, where many drugs are detoxified by cytochrome P-450, our results suggest that hemoglobin in erythrocytes may play an important role in detoxifying some drugs, such as pyrogallol. We previously showed that o-aminophenol and its derivatives were metabolized to phenoxazines in human erythrocytes or by hemoglobin, and that these phenoxazines show less adverse effects in vivo using mice (Mori et al 2000), which agrees with the results of Eckert and Eyer (1983) that o-aminophenol does not exhibit nephrotoxicity due to rapid formation of the phenoxazines in dogs. Metabolism of drugs by hemoglobin have been reported by some authors.…”
Section: Discussionsupporting
confidence: 83%
“…Later, Tomoda et al (1984Tomoda et al ( , 1986aTomoda et al ( and 1992 found that 3-hydroxyanthranilic acid, o-aminophenol, and 2-amino-5-methylphenol were metabolized to phenoxazine compounds in the presence of human hemoglobin or human erythrocytes, coupled with the oxidoreductive reactions of hemoglobin. The phenoxazine produced by the reaction of human or bovine hemoglobin with 2-amino-5-methylphenol has been shown to exert anti-cancer effects (Mori et al 2000;Koshibu-Koizumi et al 2002), immunosuppressive effects (Gao et al 2002), and antiviral effects (Iwata et al 2003).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…Phenoxazine compounds including 2-amino-4, 4·-dihydro-·, 7-dimethyl-3H-phenoxazine-3-one (Phx-1), and 2-aminophenoxazine-3-one (Phx-3), which are synthesized by the reactions of o-aminophenols with bovine hemoglobin (18,19), are oxidative phenoxazines like actinomycin D (20) and exert anticancer activity against various cancer cells in vitro and in vivo, promoting cellular apoptosis (21)(22)(23) 2-Aminophenoxazine-3-one induces cellular apoptosis by causing rapid intracellular acidification and generating reactive oxygen species in human lung adenocarcinoma cells caspase-dependent apoptosis in multiple myeloma cells (24), and caspase-independent apoptosis in neuroblastoma cells, glioma cells and gastric cancer cells (25)(26)(27). However, it remains unclear how pHi is affected, and how ROS and NF-κB are implicated in the apoptosis of cancer cells in the presence of Phx-3.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome such an alarming situation, drugs to prevent colorectal cancer are urgently required. Although few chemotherapeutic agents act effectively against colorectal cancer, it has been demonstrated that 2-amino-4,4·-dihydro-4·,7-dimethyl-3H-phenoxazine-3-one (Phx-1) and 2-aminophenoxazine-3-one (Phx-3), the oxidative form of phenoxazines, exert strong anticancer activity against a variety of cancer cells in vitro and in vivo (4)(5)(6)(7)(8)(9). However, it is still unclear whether or not these phenoxazines are effective against colon cancers that are intractable to chemotherapeutic agents (2,3).…”
Section: Introductionmentioning
confidence: 99%